Effect of multiple counselling contacts along the continuum of care on use of postpartum family planning in a cohort of Ethiopian women: a dose-response analysis - Saifuddin Ahmed; Anne Pfitzer; Firew Ayalew; Gebi Husein Jima; Deborah Sitrin (BMJ Open)
Objective Dose-response analysis of the effect of each additional contact where family planning (FP) was discussed during antenatal, delivery, postnatal or immunisation visits on the uptake of postpartum family planning (PPFP) within 12 months.Design A cohort where pregnant women were enrolled and reinterviewed approximately 12 months postpartum. Life table analyses examined differentials in probabilities of adopting contraception over 12 months postpartum by level of exposure to FP counselling. Competing risks regression analysis examined the dose effects in HRs by the number of maternal, newborn or child health (MNCH) contacts where FP was discussed, adjusted for confounding covariates.Setting Two Arsi zone woredas: Oromia and Ethiopia.Participants and measures 722 pregnant women enrolled, and 706 successfully reinterviewed 12 months postpartum about each MNCH contact during pregnancy, delivery and later visits, whether these included any PPFP counselling and PPFP use.Main results Two-thirds of the cohort delivered at home. The average number of MNCH contacts women received was 7.6, while the average number where FP was discussed was 2.8. The cumulative probability of PPFP uptake was higher for women who received FP information during at least one MNCH contact, regardless of place of delivery. Each additional MNCH contact where FP was discussed increased the likelihood of PPFP uptake by 14% (95% CI 8% to 20%) or 9% (95% CI 5% to 13%), depending on place of birth. PPFP did not increase with additional contacts without FP information.Conclusions While PPFP conversations immediately after a facility birth generated the greatest chance of affecting use, integrating at every visit in the continuum had more impact.Trial registration number ClinicalTrials.gov, NCT03585361.